2022
DOI: 10.1186/s40104-022-00686-3
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone toxicosis on reproduction as estrogen receptor selective modulator and alleviation of zearalenone biodegradative agent in pregnant sows

Abstract: Background Zearalenone (ZEA) is a resorcylic acid lactone derivative derived from various Fusarium species that are widely found in food and feeds. The molecular structure of ZEA resembles that of the mammalian hormone 17β-oestradiol, thus zearalenone and its metabolites are known to compete with endogenous hormones for estrogen receptors binding sites and to activate transcription of oestrogen-responsive genes. However, the effect of long-term low-dose ZEA exposure on the reproductive response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…To be note, ZEN exhibited toxicity on the reproductive system with direct and indirect methods. First, acting as an endocrine disruptor, ZEN is directly toxic to the female reproductive system through the estrogen receptor, which has been proved by a large number of studies. , For example, ZEN could affect the secretory function of supporting cells and disrupt the secretion of reproductive hormones via estrogen receptors, which in turn leads to reduced fertility. , Importantly, some recent studies have found that ZEN exposure in adolescent mice affects the intestinal flora structure, leads to abnormalities in the LPC anabolic pathway, and induced ovarian developmental disorders . Since diet is the most common route of human exposure to ZEN, whether the reproductive disorder caused by ZEN is potentially related with the microbiota in the gastrointestinal tract is a critical issue that needs to be studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be note, ZEN exhibited toxicity on the reproductive system with direct and indirect methods. First, acting as an endocrine disruptor, ZEN is directly toxic to the female reproductive system through the estrogen receptor, which has been proved by a large number of studies. , For example, ZEN could affect the secretory function of supporting cells and disrupt the secretion of reproductive hormones via estrogen receptors, which in turn leads to reduced fertility. , Importantly, some recent studies have found that ZEN exposure in adolescent mice affects the intestinal flora structure, leads to abnormalities in the LPC anabolic pathway, and induced ovarian developmental disorders . Since diet is the most common route of human exposure to ZEN, whether the reproductive disorder caused by ZEN is potentially related with the microbiota in the gastrointestinal tract is a critical issue that needs to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…First, acting as an endocrine disruptor, ZEN is directly toxic to the female reproductive system through the estrogen receptor, which has been proved by a large number of studies. 38,39 For example, ZEN could affect the secretory function of supporting cells and disrupt the secretion of reproductive hormones via estrogen receptors, which in turn leads to reduced fertility. 38,40 Importantly, some recent studies have found that ZEN exposure in adolescent mice affects the intestinal flora structure, leads to abnormalities in the LPC anabolic pathway, and induced ovarian developmental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of male rabbits, inhibited spermatogenesis and reduced reserves of testicular and epididymal sperm were noted after exposure to increasing AFB1 concentration of up to 7.5 mg/kg ( 32 ). Similarly, in sow models, ZEA could, at low doses, regulate the concentration of estrogen receptors-α and -β in specific organs while inducing apoptosis, vulva swelling, and an imbalance of reproductive hormones ( 33 ). Other mycotoxins, such as T-2, DON, and ZEN, can also cause reproductive toxicity by inhibiting steroidogenesis and cell proliferation.…”
Section: Systemic Toxicity Of Mycotoxinsmentioning
confidence: 99%
“…In particular, dietary ingestion of mycotoxins can cause severe damage to the immune [ 10 ], reproductive [ 11 ] and respiratory systems [ 12 ], as well as to various organs such as the intestine [ 13 , 14 ], kidney [ 15 ] and liver [ 16 , 17 ]. In sows, mycotoxins cause (a) decreased feed intake, (b) problems in piglet development [ 18 ], (c) liver damage [ 19 ], (d) gastrointestinal tract dysfunction (GI) and oxidative stress [ 20 ], (e) various reproductive and infant system dysfunctions [ 21 , 22 ] and (d) offspring health problems (e.g., swollen vulva in suckling piglets, increased indicators of oxidative stress) [ 23 , 24 , 25 ]. In addition, they are considered a crucial risk factor for postpartum dysgalactia syndrome (PDS) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%